Micronutrient deficiency risk in long-term enterally fed patients: A systematic review. (December 2022) - Osland, Emma J.; Polichronis, Kelly; Madkour, Rowan; Watt, Amanda; Blake, Claire
Summary: Background and aims: The micronutrient status of those receiving long-term enteral nutrition (EN) is poorly characterised. This systematic review was undertaken to determine prevalence of micronutrient deficiency in those receiving EN; the impact of the route of feeding; whether underlying disease or clinical factors were associated with micronutrient status; and the efficacy of interventions utilised to treat identified micronutrient deficiency. Methods: Electronic databases (CINAHL, Embase, PubMed, Web of Science) were searched to June 2021 for publications of primary investigation of micronutrient status in adults or children (>5yrs) receiving EN for >2 months in their usual residence. Independent assessment of compliance with inclusion criteria (Covidence®), data extraction of predefined data points, assessment of basis (Academy of Dietetics Quality Checklist) and certainty of evidence (GRADE) was assessed by at least two authors. (PROSPERO Registration: CRD42021261113). Results: Thirty-one studies (n = 744) met inclusion criteria. Deficiency was reported for copper, zinc, selenium, beta-carotene, and vitamins A, D and E: Only copper, zinc and selenium were associated with physical/haematological manifestations of deficiency. Jejunal feeding was associated with the development of copper deficiency and often required gastric or parenteral replacement to resolve the issue. Circumstances leading to deficiency included receiving feed products formulated with inadequate amounts of the implicated nutrient, low feed product volumes in the context of low macronutrient requirements, and nutritional decline prior to commencement of EN. Potential confounding factors such as inflammation were rarely accounted for. No studies investigated the contribution of underlying clinical condition on micronutrient status, and no other clinical or demographic features appeared to impact outcomes. Reported methods for treating identified deficiencies were usually successful in reversing deficiency symptoms. The certainty of evidence is very low, and the level of bias moderate to high. Conclusion: While the evidence is very uncertain about the effect of long-term enteral feeding on the development of micronutrient deficiencies, clinicians should be alert to the possibility of micronutrient deficiency developing in long-term EN fed patients. Those who may be at increased risk are those receiving nutrition into the jejunum, those who meet macronutrient requirements in low volumes of EN product, and those commencing EN in a nutritionally deplete state. Further research and surveillance of micronutrient status with contemporary EN products and practices is required.